Basal markers of inflammation, muscle damage, and performance during five weeks of pre-season training in elite youth Rugby League players - Ferris, D.; Gabbett, T.; Mclellan, C.; Minahan, C. (Journal of Athletic Enhancement, 2018)
Objectives: this study examined changes in basal biochemical markers of immune function and muscle damage, as well as physical performance during a typical pre-season training block in preparation for the Australian national youth rugby league competition.